Immunostimulatory monoclonal antibodies for hepatocellular carcinoma therapy : trends and perspectives - Mazzolini Rizzo, Guillermo Daniel (2017)
Hepatocellular carcinoma (HCC) is the second cause of cancer-related death in the world and isthe main cause of death in cirrhotic patients. Unfortunately, the incidence of HCC has grown significantly in the last decade. Curative treatments such as surgery, liver transplantation or percutaneous ablationcan only be applied in less than 30% of cases. The multikinase inhibitor sorafenib is the first line therapy foradvanced HCC. Regorafenib is the standard of care for second-line patients. However, novel and more specificpotent therapeutic approaches for advanced HCC are still needed. The liver constitutes a unique immunologicalmicroenvironment, although anti-tumor immunity seems to be feasible with the use of checkpoint inhibitors suchas nivolumab. Efficacy may be further increased by combining checkpoint inhibitors or by applying loco-regionaltreatments. The success of immune checkpoint blockade has renewed interest in immunotherapy in HCC.